GOVERNANCE IN MODERN LEGAL SYSTEMS: COMPARATIVE MODELS, DISCRETION, AND THE NEXUS OF LAW AND POWER - Mustafa, Cecep; Komalasari, Rita (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2025)
Modern legal systems function not merely as frameworks for dispute resolution but as dynamic expressions of governance, reflecting societal values, institutional designs, and political philosophies. This paper examines how diverse governance models influence legal practice, with a focus on the United States, China, and Western Europe. The study aims to uncover the mechanisms through which law both constrains and empowers state actors, influences judicial discretion, and balances individual rights with collective objectives. Methodologically, the analysis combines comparative legal study with a functional examination of internal governance structures, including administrative regulation, evidentiary standards, and procedural oversight. By integrating doctrinal analysis with cross-jurisdictional comparison, the paper evaluates both the external relationships between states and citizens and the internal regulation of specialized actors within the legal system. The findings reveal that governance models profoundly influence legal outcomes. The U.S. principal–agent model emphasizes limits on state power and protection of individual rights, the Chinese unitary model prioritizes policy efficiency and centralized control, and the European public feature model promotes collective justice through active judicial engagement. Moreover, internal governance mechanisms—ranging from forensic regulation to discretionary oversight—play a critical role in ensuring consistency, fairness, and reliability. Overall, the study concludes that legal governance operates at the intersection of law, power, and procedure, mediating both societal expectations and institutional capabilities. Understanding these dynamics is essential as globalization, technological innovation, and political change continue to reshape the contours of justice, authority, and legitimacy worldwide.